Innovations in Polymer Applications - Plastic Packaging - Rego, Diogo Cardoso; Sartor, Cíntia; Klayn, Nicolas Augusto; Corrêa, Harrison Lourenço (Journal of Research Updates in Polymer Science, 2020)
Polymer materials are used in several industrial sectors such as, paints and varnishes, packaging, and the automotive sector. The countless applications of this type of material stem from several factors such as lightness and ease of processing when compared to metals and ceramics. The possibility of chemical modification of polymers is worth mentioning, which can result in a new material with mechanical properties superior to those of the original ones. Another unique characteristic of polymer material is related to the ease with which they can be mixed with other elements (vegetable and synthetic fibers, metals, ceramics) to obtain a composite or hybrid material, thus expanding the spectrum of polymer applications. In this sense, the present work aims to show the uses of polymers in the packaging segment, addressing the main physicochemical and mechanical characteristics that are necessary for manufacturing packaging items as well as innovative technologies to obtain those materials.